How we treat delayed haemolytic transfusion reactions in patients with sickle cell disease. (13th May 2015) - Gardner, Kate; Hoppe, Carolyn; Mijovic, Aleksandar; Thein, Swee L.
Summary Transfusion therapy is effective in the prevention and treatment of many complications of sickle cell disease (SCD). However, its benefits must be balanced against its risks, including delayed haemolytic transfusion reactions (DHTR). Not only is the relative rate of alloimmunization higher in patients with SCD than in other patient populations, but attendant risks associated with DHTR are even greater in SCD. Clinicians' awareness of DHTR events is poor because symptoms of DHTR mimic acute vaso‐occlusive pain and immunohaematology findings are often negative. Transfusions delivered in the acute rather than elective setting appear to confer a higher risk of DHTR. Management of DHTR in SCD depends on the clinical severity, ranging from supportive care to immunosuppression, and optimization of erythropoiesis. DHTR must be considered in any recently transfused patient presenting with acute sickle cell pain. Meticulous documentation of transfusion and immunohaematology history is key. We anticipate an increase in DHTR events in SCD patients with the increasing use of red blood cell transfusion therapy.